Museum Display Showcase Furniture System Research Based on Internet of Things Technology in Intelligent Environment. (29th January 2021) - Hu, Jiaojiao; Wu, Zhihui; Jin, Lei
Abstract : The protection of cultural relics has always been an important issue in the field of museums and archaeology. With the development of Internet of Things technology, the security system of the museum is more intelligent and integrated. In order for the museum display system to keep up with the intelligent age, this article mainly studies the research and realization of the museum showcase system based on the Internet of Things technology in a smart environment. Before the start of the experiment, we developed the overall design of the system, including three functional modules: temperature module, illumination module, and monitoring module. The experiment is done mainly for system testing. The performance test of the sensor module needs to sample the temperature and humidity sensor to verify the accuracy of the temperature and humidity signal collected in the instrument circuit. The light information collection test uses the ADC sampling inside the CC2530 to obtain the required data and judges whether these temperature, humidity, and light intensity values exceed the preset values. The serial port needs to be initialized to carry out data communication and transmission normally. After the receiving end finishes receiving, the sending end will clear the data buffer to prepare for the next data transmission. The experimental data show that the error between the predicted value and measured value of the temperature system is about 3°C, which is within the allowable error range of the experiment. The results show that the system has perfect functions, is safe and reliable, meets the expected requirements, and has good practicability.